Interdisciplinary Coordination in Historical-Theoretical and Music-Performing Training of Future Musical Art Teachers - Boichenko, Maryna; Nikolai, Halyna; Linenko, Alla; Koehn, Natalya (Journal of History Culture and Art Research, 2020)
The article investigates the basic blocks of future musical art teachers' training, which include historical-music, theoretical-music, and music-performing disciplines. In this regard, the didactic potential of their interdisciplinary coordination is revealed, and ways of its realization are suggested. The methodological basis of the study includes the phenomenological approach in which music is positioned as a distinctive phenomenon, an ideal substance that comprehends the immense and creates a sensual picture of the world. It is shown that, in contrast to the competence approach, which directs the efforts of researchers to the formation of professional and personal qualities of the teacher, the interdisciplinary approach primarily involves optimization of the curriculum. Interdisciplinary coordination is considered as flexible and consistent use of all its components in a real learning process. Interdisciplinary coordination, based on the allocation of related elements in the content of subjects of historical-theoretical and music-performing blocks, provides formation of common knowledge and skills in future musical art teachers, ability to use their various activities (educational, performing and didactic) independently, flexibly and creatively. Essential characteristics of future musical art teacher’s music-performing training are presented, which consist of voice training, choral conducting and music-instrumental training, aimed at interpreting composers’ works. The latter requires harmonization of cognitive and emotional components of the experience. For all types of music-performing training (piano, violin, accordion, vocal, choral conducting, etc.), it is important to analyze the performance means of expressiveness, technical difficulties, differences between ideal auditory-figurative representations and real sound.